Pengaruh Shalat Fardhu Terhadap Kesehatan Mental Mahasantriah Ma’had Al Jami’ah UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Fauzan Royhanuddin Nasution (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2023)
That fardhu prayer has a significant influence on mental health. This is because it is found that students who perform prayers more regularly and solemnly 'have a healthier mental state than students who pray irregularly. The purpose of this study was to determine whether there was a significant influence on the implementation of fardhu prayer on the mental health of UIN students of Sheikh Ali Hasan Ahmad Addary Padangsidimpuan.Research methods is quantitative research.The method used in this study is ex post facto. The population in this study is students in Ma'had Al Jami'ah UIN Sheikh Ali Hasan Ahmad Addary consisting of 1259 and a sample of 93. The data analysis uses the product moment correlation formula.The result of the study indicate that the mental health condition of students in Ma'had Al Jami'ah UIN Sheikh Ali Hasan Ahmad Addary can be said to be good with a score of 76.8% while the mental state of students can be said to be good with a score of 69.5%. From the results of this study explained that there was a significant influence between fardhu prayer on the mental health of students, which found a regression coefficient of Y = 17.875 + 0.595X, and Tcalculation calculated Ttable (5.615 1.66177) then Ha was accepted and H0 was rejected meaning that there was a significant influence simultaneously between the variables of fardhu prayer (X) and mental health (Y).